Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1177/1088357609352901
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effectiveness of Video Instruction on Social and Communication Skills Training for Children With Autism Spectrum Disorders: A Review of the Literature

Abstract: Video instruction as an intervention for teaching skills to children with Autism Spectrum Disorders (ASD) is gaining increased momentum in applied settings.Video instruction, comprised of video modeling, video self-modeling, and point-of-view video, has been utilized in various fields of study with various populations and target behaviors. Literature on video instruction will be reviewed to determine its effects on the acquisition and generalization of social and communication skills for students with ASD in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
112
0
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(131 citation statements)
references
References 68 publications
11
112
0
7
Order By: Relevance
“…The results support earlier research showing children watching structured television shows can learn skills by watching those shows (e.g., Lauricella, et al, 2011;Wartella, et al, 2012), and extends that literature by showing children with ASD can learn the same way. The results also resemble positive outcomes seen in video modeling interventions with children with ASD (e.g., Ayres & Langone, 2005;Shukla-Mehta, et al, 2009). Given the many overlapping elements of those two interventions (clear descriptions of behavior, modeling of the appropriate behavior); the results may suggest the possibility of a shared mechanism of effect for both.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…The results support earlier research showing children watching structured television shows can learn skills by watching those shows (e.g., Lauricella, et al, 2011;Wartella, et al, 2012), and extends that literature by showing children with ASD can learn the same way. The results also resemble positive outcomes seen in video modeling interventions with children with ASD (e.g., Ayres & Langone, 2005;Shukla-Mehta, et al, 2009). Given the many overlapping elements of those two interventions (clear descriptions of behavior, modeling of the appropriate behavior); the results may suggest the possibility of a shared mechanism of effect for both.…”
Section: Resultssupporting
confidence: 65%
“…Interventions to address deficits include elements such as labeling and breaking down targeted skills, modeling appropriate behaviors, and encouraging practice (Odom, Boyd, Hall, & Hume, 2010). Video modeling interventions including those elements have effectively taught skills to children with ASD (e.g., Ayres & Langone, 2005;Shukla-Mehta, Miller, & Callahan, 2009). Video modeling interventions involve repeatedly presenting the child with a video of themselves or another person engaging in a desired behavior and providing an opportunity to practice the behavior.…”
mentioning
confidence: 99%
“…Mason et al suggested that the effectiveness of point-of-view video modeling in teaching social skills was inconclusive given the limited research. Nonetheless, Mason et al indicated that this form of VM was promising for individuals with ASD, which aligned with the conclusions of past meta-analysis of the efficacy of video modeling by McCoy and Hermansen (2007) and Shukla-Mehta et al (2012).…”
Section: Advantages Of Point-of-view Video Modelingsupporting
confidence: 57%
“…A video of the actual recipient of the instruction engaging in the preferred behavior or skill is known as video self-modeling (VSM). Point-of-view video models or first-person perspective video modeling is a video of what the recipient of the instruction would actually see if he or she were engaging in the behavior or skill (Shukla-Mehta et al 2012). This form of VM may include hands demonstrating the skill and using the relevant materials or other individuals connected to performing the skill or behavior (McCoy and Hermansen 2007).…”
Section: Video Modeling As a Means To Develop Social Skills In Indivimentioning
confidence: 99%
“…The use of technology in the delivery of much needed therapy promises to be effective for shrinking the gap between the therapy that is recommended for children with ASD and the amount they receive. Recently, there has been a trend towards computer-based interventions which capitalize on the often-observed preference that children with ASD show for flat screen information [13][14][15] as well as evidence suggesting that tablets specifically have been a great learning tool for children on the spectrum [16,17]. However, since there is scant research on computer-based interventions for children with ASD, many questions remain to be answered: At what age are children diagnosed with ASD capable of being fully engaged with computer-based interventions?…”
Section: Introductionmentioning
confidence: 99%